Association of the Maternal Folic Acid Supplementation with the Autism Spectrum Disorder: A Systematic Review - Sampaio, Adalberto Cruz; Matos, Francisco Facundo de, Neto; Lopes, Lucas de Lucena; Marques, Ítalo Marcelo Maia; Tavares, Ravel Moreira; Fernandes, Marcus Vinicius de Macedo; Teixeira, Maria Raquel Vieira da Silva; Brito, Alessandra Bezerra de; Feitosa, Andrea Couto; Guedes, Tarciana Oliveira; Mota, Magaly Lima (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To analyze the scientific production regarding maternal folic acid (FA) supplementation and its relationship with autistic spectrum disorder (ASD).Data Sources We performed unrestricted electronic searches in the BIREME virtual bank, Virtual Health Library (VHL) and Medical Literature Analysis and Retrieval System Online (MEDLINE/PubMed) databases.Selection of Studies For sample selection, articles that met the proposed objectives were included, published in English, Spanish and Portuguese, the use of Health Sciences Descriptors (DeCS): autistic OR autism AND autism spectrum disorder AND folic acid, AND, with the use of the Medical Subject Headings (MeSH): autistic OR autism AND autistic spectrum disorder AND folic acid.Data Collection Data extraction was performed by the reviewers with a preestablished data collection formulary.Data Synthesis The Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) was used based on a checklist with 27 items and a 4-step flowchart.Results A total of 384 articles was found by the search strategies, of which 17 were eligible following the pre-established criteria. The main findings of the present review point to maternal FA supplementation in the pre-conception period and beginning of pregnancy as a protective effect in relation to ASD, which should be indicated in this period as prevention to the problem.Conclusion According to the research analyzed, more studies are necessary to know its effects on pregnancy, since the consumption of excessive FA may not be innocuous.
Keywords: autistic spectrum disorder; folic acid; pregnancy; supplementation